The docking of synaptic vesicles on the presynaptic membrane induced by α-synuclein is modulated by lipid composition - Wing K. Man (Nature Portfolio, 2021)
α-Synuclein is a presynaptic protein whose aberrant aggregation is associated with Parkinson’s disease. Here, the authors show how αSynuclein-induced docking of synaptic vesicles is modulated by the lipid composition changes typically observed in neurodegeneration using an in vitro system.